Cartografias midiáticas: o corpomídia na construção da memória da dança - Camargo, Andréia Vieira Abdelnur (2012)
This thesis discusses the role of cultural journalism in the reactivation of the Pró-Posição dance group. From the tensions between cultural journalism and body (here suggested as a mediator and an agent of culture), both of them seen as bodymedia (KATZ & GREINER, 2001, 2003, 2004, 2005), we suggest the hypothesis of the memory in the dance as a cartography of media maps generating continuity between past and present. The Pró-Posição activities began in 1973 and lasted until 1983; in the 90s some occasional appearances took place until its full resurgence in 2008. Although the reactivation of the group can be seen as a recuperation, the hypothesis here suggests a speech of continuity (LOTMAN, 1996). Since its reactivation, the group has been using the reference of swan -- an animal image associated with dance and considered the most spectral memory used in cultural journalism and publicity. The process of communication as a result of the combination of these media is based on the notion of navigation charts (HUTCHINS, 1996), in which the culture, the body and the cognition are seen as mediators interconnected. This consideration reinforces the hypothesis of memory as a mapping, in other words, the junction of several maps that communicate with each other in the great sphere of culture. The corpus of this research was organized in three dossiers: the first refers to several reports of Pró-Posição group in cultural journalism (regional and national); the second results from the compilation of materials concerned to the group in other media forms in order to propose a reflection about them and about its visibility in the media; and the third deals with publications and other references discussing the construction of the metaphor of swan in the dance domain. In the theoretical aspect of the research, the Bodymedia Theory (KATZ & GREINER) mediates the dialogues in cultural studies of journalism (PIZA, 2003; COELHO, 2006), the tensions between media and culture (PRADO, 2006; HUTCHINS, 1996; LOTMAN, 1996) and the relationships between historiography and memory (HARTOG, 2011; TAYLOR, 2003)